The Probiotic Butyricicoccus pullicaecorum Reduces Feed Conversion and Protects from Potentially Harmful Intestinal Microorganisms and Necrotic Enteritis in Broilers - Eeckhaut, Venessa; Wang, Jun; Van Parys, Alexander; Haesebrouck, Freddy; Joossens, Marie; Falony, Gwen; Raes, Jeroen; Ducatelle, Richard; Van Immerseel, Filip (Frontiers in Microbiology, 2016)
In the past the use of in-feed antibiotics has been the main strategy to improve health, nutrient availability and growth performance by selectively modifying the gut microbiota. Due to consumer concerns about the threat of antibiotic-resistant bacteria and their preference for medication-free poultry production, poultry integrators have been forced to consider alternatives. Probiotics which do not result in the development and spread of microbial resistance are among the candidate replacements for antibiotics. In this study the effect of in-feed supplementation of the butyrate producing Butyricicoccus pullicaecorum strain 25-3T on performance, intestinal microbiota and prevention of necrotic enteritis, a disease caused by Clostridium perfringens was evaluated in broilers. For the performance study, day old Ross 308 chicks were randomly allocated into two treatment groups and fed either a non-supplemented diet or a diet supplemented with 109 cfu lyophilized B. pullicaecorum per kg feed for 40 days. On day 40 broilers administered B. pullicaecorum had a significant lower bodyweight (2675 g vs 2762 g; p = 0.0025) but supplementation of B. pullicaecorum decreased the feed conversion ratio significantly (1.518 vs 1.632; p < 0.0001). Additionally, ingestion of the Butyricicoccus strain significantly lowered the abundance of Campylobacter spp. in the caecum and Enterococcus and Escherichia/Shigella spp. in the ileum at day 40. In feed supplementation of Butyricicoccus pullicaecorum in the necrotic enteritis trials resulted in a significant decrease in the number of birds with necrotic lesions compared with the untreated control group. These studies show that supplementation of B. pullicaecorum is able to improve feed conversion, to reduce the abundance of some potentially important pathogens in the caeca and ileum and to contribute to the prevention of necrotic enteritis in broilers, making the strain a potential valuable probiotic.